Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ijerph16162874
|View full text |Cite
|
Sign up to set email alerts
|

“Everyone Has the Right to Drink Beer”: A Stakeholder Analysis of Challenges to Youth Alcohol Harm-Reduction Policies in Lebanon

Abstract: Background: Alcohol use is a major risk factor in premature death and disability, especially among youth. Evidence-based policies to prevent and control the detrimental effect of alcohol use have been recommended. In countries with weak alcohol control policies—such as Lebanon, stakeholder analysis provides critical information to influence policy interventions. This paper assesses the views of stakeholders regarding a national alcohol harm reduction policy for youth. Methods: We interviewed a total of 22 key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…For example, Knai et al [9] found that both the production and uptake of responsibility pledges by responsibility deal partners in the UK, including organisations with commercial interests, were largely driven by the interests of partners themselves, and this made it possible for them to resist change. A somewhat similar finding emerged in a study conducted in Lebanon [13], where it was noted that industry representatives argued against evidence-based policies in reducing alcohol harm experienced by youth. A study by Hessari and colleagues [10] found that alcohol industry funded organisations were significantly more likely to tweet about behavioural aspects of drinking and less likely to mention (breast) cancer risk [10].…”
supporting
confidence: 71%
See 2 more Smart Citations
“…For example, Knai et al [9] found that both the production and uptake of responsibility pledges by responsibility deal partners in the UK, including organisations with commercial interests, were largely driven by the interests of partners themselves, and this made it possible for them to resist change. A somewhat similar finding emerged in a study conducted in Lebanon [13], where it was noted that industry representatives argued against evidence-based policies in reducing alcohol harm experienced by youth. A study by Hessari and colleagues [10] found that alcohol industry funded organisations were significantly more likely to tweet about behavioural aspects of drinking and less likely to mention (breast) cancer risk [10].…”
supporting
confidence: 71%
“…The articles clearly illustrate that addressing alcohol-related harms involves multi-level governance including organizational, local, state/provincial, and national levels. Despite rising levels of consumption in LMICs, most of the papers (12/15) focused on high income countries, with just one each from Lebanon [13] and South Africa [20]. The most common methodology used in the studies published in this Special Issue was qualitative case studies, followed by pre-post designs ( Table 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A significantly higher prevalence of alcohol use was estimated in the adult as well as the young general population of West Asia. The high prevalence in West Asia is mainly reflecting the high estimate of alcohol use in Lebanon, which has the highest proportion of non‐Muslims and a lax policy regarding alcohol use compared to the rest of the region [28–30]. Insufficient studies were available for the East Africa and Gulf subregions.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, to achieve a transparent and evidence-based approach for decision-making, it is necessary to thoroughly evaluate and investigate various factors that affect the adoption and implementation of the foreign currency subsidy policy. In this regard, stakeholder analysis is a key tool for assessing multiple issues [ 48 50 ].…”
Section: Introductionmentioning
confidence: 99%